Optimalisasi Pengelolaan Sampah melalui Kolaborasi Bank Sampah untuk Penerapan Ekonomi Sirkular dan Minyak Jelantah di Tingkat Komunitas - Rentha Theresia; Leroy Holman Siahaan; Mila Viendyasari (Journal of Empowerment Community, 2026)
Effective waste management remains a significant challenge in achieving sustainable development at the community. One of the most relevant strategic approaches is the implementation of the circular economy concept through collaboration between communities and waste management institutions such as waste banks, aimed at optimizing waste management toward a sustainable green energy system. This study employs a descriptive qualitative method, combining literature review and field observations in communities that have implemented circular economy models based on waste bank practices. The findings indicate that the integration of waste management with waste bank systems enhances the economic value of household waste, strengthens community participation, and creates innovative opportunities for used cooking oil as an alternative energy source, including biodiesel. Moreover, this collaborative model contributes to carbon emission reduction and improves environmental awareness at the grassroots level. Hence, the synergy between waste management and waste banks serves as a strategic framework for advancing the circular economy, supporting the transition toward green energy and sustainable community empowerment.